Exploring Students and Teachers in English Classroom Interaction after Covid-19 Pandemic at Senior High School - Fadila, Meisyani Gustri (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
To ensure that the students understand the lesson they are learning, the teacher must prod them and give them directions during the learning process. Classroom interaction is the distance between the teacher and the students. On the other hand, when things start to change again after the pandemic, various problems start to appear. Because they are used to learning electronically, some teachers are concerned that their students would not interact in the classroom as expected for learning. As a result, the researcher is curious to investigate classroom interaction following the covid epidemic. The purpose of this study is to investigate how students and teachers interacted in English classes following the covid epidemic. The researcher then used a descriptive research strategy to achieve the investigation's goal. This study is being done in Pesisir Selatan Regency, specifically for senior high school students who have experienced a pandemic in the past and who have also seen how classroom interaction has changed both during and after a pandemic. As a result, the researcher used purposive sampling to select the individuals. Following that, 30 students from Pesisir Selatan regency's senior high school made up the overall participant count utilizing the sampling technique. The data was gathered by the researcher using a questionnaire. There are three different sorts of classroom interaction, according to the questionnaire the researcher provided the participants that was based on the Abarca hypothesis. Following that, the data was examined using the mean of participant responses to get the descriptive statistics, which the researcher then displayed in the chart. Students identified as being between the ages of 10 and 15 made up the biggest percentage (46%). After the covid epidemic, student-centered interactions predominated in the classroom. Students who responded to surveys and gave their explanations for why they were more engaged in classroom interaction after the epidemic revealed that they had little interest in online interaction before the pandemic.